Properties of gels from whey protein concentrate and honey at different pHs - Yamul, Diego Karim (2003)
Structural and functional properties of heat-induced gels from whey protein concentrate (WPC)-honey prepared at pHs 3.75, 4.2 and 7.0 were analyzed. Gel structure was observed by scanning electron microscopy, and the apparent transition temperature for protein denaturation was determined by differential scanning calorimetry. The solubility of the protein components in different extraction media, and the water-holding capacity, firmness, elasticity, relaxation time, adhesivity, cohesiveness and color of gels were determined. Results show that disulfide interchange reactions are important in determining the elasticity, water-holding capacity, relaxation time and cohesiveness of WPC gels. Honey decreases the relaxation time of gels prepared at pHs 7.0 and 4.2, and increases the browning and the water-holding capacity of gels, the apparent transition temperature of WPC dispersions at the three pHs assayed, and the adhesivity of acidic gels. The solubility of the protein constituents of gels in a pH 8.0 buffer increases slightly at honey concentrations of 27.5% or more, which correlates with a decrease in the gel cohesiveness, having these gels a structure with smaller pores. The products obtained could be utilized in the formulation of different desserts, such as flans and cake and tart fillings.